Molybdenum disulfide nanosheets embedded in hollow nitrogen-doped carbon spheres for efficient lithium/sodium storage with enhanced electrochemical kinetics. (1st September 2018) - Guo, Pengqian; Sun, Kai; Liu, Dequan; Cheng, Pu; Lv, Mingzhi; Liu, Qiming; He, Deyan
Abstract: Molybdenum disulfide nanosheets@hollow nitrogen-doped carbon (MoS2 @NC) spheres were prepared via a facile synthesis and investigated as a host material for ion storages. When used in lithium ion batteries (LIBs) or sodium ion batteries (SIBs), the MoS2 @NC spheres electrodes exhibited excellent electrochemical performances. A high capacity of 1386 mAh g −1 after 100 cycles was obtained at a current density of 200 mA g −1 for LIBs. As for SIBs, a capacity of 330 mAh g −1 was retained after 400 cycles at 1000 mA g −1 . The remarkable ion storage performances can be attributed to the hierarchical architecture of the MoS2 @NC spheres, which not only supply abundant active sites and efficient electron and ion pathways, but also alleviate the volume change of the active MoS2 material. Meanwhile, synergistic effect of the heterogeneous components, interfacial ion storages, nitrogen doping and induced defects are responsible for high capacities of the MoS2 @NC electrodes. And the electrodes exhibited enhanced electrochemical kinetics due to the significantly improved electrical conductivity and the large specific area of the MoS2 @NC spheres. Graphical abstract: Image 1 Highlights: Defective MoS2 nanosheets embedded in hollow nitrogen-doped carbon spheres were prepared via a facile synthesis. The hierarchical structures of the MoS2 @NC spheres supply abundant active sites and efficient electron/ion pathways. The MoS2 @NC spheres electrode exhibits excellent lithium/sodium storage performance.